Uptake of Digital Innovations on Financial Performance of Commercial Banks in Kenya - Kimathi, Doris (Meru Universty of Science and Technology International Conference (MUSTIC), 2025)
The rapid evolution of digital innovations has transformed the banking sector globally, and commercial banks in Kenya are witnessing profound transformations in their operations driven by digital innovations. Despite the momentous benefits associated with digital innovations, a gap persists in realizing the precise influence of these innovations on financial performance of commercial banks. The gap is further aggravated by lack of extensive empirical studies, that systematically assess the relationship between key variables such as process, product, marketing and organizational innovations and financial performance of commercial banks within the context of digital innovations in Kenyan banking sector. Maneuvering the ever changing government policies poses a daunting challenge as industry seek to balance innovation and compliance hence dampen the zeal of commercial banks to embrace transformative digital initiatives. This study sought to assess the effect of uptake of digital innovations on financial performance of commercial banks in Kenya. The specific objectives were to assess the effect of uptake of digital process innovations, investigate the effect of uptake of digital product innovations, establish the effect of uptake of digital marketing innovations and analyze the effect of uptake of digital organizational innovation on financial performance of commercial banks in Kenya. The study was guided by; Rogers Diffusion of Innovation theory, Evolutionary Theory of Economic Change, Disruptive Innovation theory and Theory of Dynamic Capabilities. The study adopted Positivism philosophy and a target population of 1,470 employees from the 39 Commercial Banks in Kenya were utilized in the study. A sample size of 315 comprising of senior management, supervisory management and junior officers was reached at by use of stratified random sampling technique. A descriptive study design was employed and primary data was collected using structured questionnaires while secondary data was obtained from banking sector supervisory and innovation survey reports. Pilot test was carried out to estimate the reliability and validity of data collection instruments. Reliability was estimated using Cronbach’s Coefficient Alpha while content validity was tested using Kaiser-Mayor-Oklin and Bartlett’s test of sphericity. Descriptive analysis was presented using frequency tables, pie charts, and bar graphs. Panel linear regression model was used where, a simple linear regression model was applied for each variable, then a joint model was done to determine the joint effect with significance level of P˂0.05. The model was tested for linearity, normality, heteroscedasticity and multicollinearity. The findings were 89%(R2=0.89, F=396.633, P˂.0001) of the variations in commercial banks ROE were explained by digital process, product, marketing and organizational innovations. There was positive and significant correlation between uptake of digital innovations and financial performance of commercial banks (ROE, P˂0.05). The study recommends that commercial banks leverage talent development strategies, strategic innovative collaborations, prioritize customer centrality, embrace decentralized decision making and stay abreast with regulatory requirements so as to positively and significantly improve financial performance. To optimally benefit from digital innovations, commercial banks need to invest in GreenTech products, navigate content creation complexities and implement agile management policies to flatten hierarchies that stifle innovation. The study further recommends that policy makers to provide clear guidelines and harmonization of regulatory environment, for banks to have enthusiasm in embracing transformative digital initiatives. The findings of the study did not necessarily generalize to other industries or geographical contexts. Factors such as regulatory frameworks, market structures, cultural norms, and technological infrastructure can vary significantly between organizations and regions, limiting the external validity of the study’s conclusions. The study proposes comparative studies across diverse contexts that can help assess the generalizability of findings.